Roadway supporting technology applied to three soft coal seam at Yanlong mining area in China - Zhang, Sheng; Li, Jie; Ma, Jianhong (Thermal science, 2019)
The compressive strength of coal in Yanlong mine area of China is less than 3 MPa. Basically, it is powdery. The roof and floor rocks are mudstone. Therefore, this coal seam is a typical ?three soft? coal seam. Anchor and cable cannot be used due to low anchoring force. This paper describes how to support this type of soft coal roadway. The deformation characteristics of soft coal roadway were investigated. Results show the conventional U-shaped steel support is not subjected to uniform load, which bearing capacity can be improved by structural compensation, such as addition of horizontal and vertical beams made of U-shaped steel. In addition, by drilling pressure-relief holes in the ribs of a soft coal roadway, the stress distribution of surround rock in the roadway can be improved, which can transfer the high stress in the surrounding rock to deeper parts and reduce the pressure on the artificial support. A support method is to combine the strengthened U-shaped steel support with pressure-relieving drill holes, providing an economic and efficient way to support the very soft coal roadways. nema